2022
DOI: 10.4103/aer.aer_140_22
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study between Local Dexmedetomidine and Intravenous Dexmedetomidine during Awake Fiberoptic Nasotracheal Intubation

Abstract: Background: Awake fiberoptic intubation (AFOI) is the gold standard for managing a difficult airway. To make the patient comfortable and cooperative during the procedure, many drugs such as benzodiazepines, opioids, or dexmedetomidine are used. Most of these intravenously given drugs may cause respiratory depression and hypoxia. Aim: We compared the efficacy of dexmedetomidine through nebulization and transtracheal route with intravenous routes with the primary aim of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…Furthermore, as ketamine and dexmedetomidine do not have a local anesthetic or analgesic action, nebulization did not have any effect other than the effect due to systemic absorption of the drugs through respiratory mucosa. Similarly, the cough severity, patient tolerance, intubating conditions, propofol requirement, and hemodynamic variables were better in group I than in group N. The trial findings of Sancheti et al contradict the findings of our study [ 12 ]. This may be because the authors used an additional (transtracheal) route of dexmedetomidine administration in their study.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Furthermore, as ketamine and dexmedetomidine do not have a local anesthetic or analgesic action, nebulization did not have any effect other than the effect due to systemic absorption of the drugs through respiratory mucosa. Similarly, the cough severity, patient tolerance, intubating conditions, propofol requirement, and hemodynamic variables were better in group I than in group N. The trial findings of Sancheti et al contradict the findings of our study [ 12 ]. This may be because the authors used an additional (transtracheal) route of dexmedetomidine administration in their study.…”
Section: Discussioncontrasting
confidence: 98%
“…Intravenous dexmedetomidine was found to suppress the response to laryngoscopy and intubation better than nebulized dexmedetomidine. Sancheti et al compared the intravenous route of dexmedetomidine with a combination of nebulized and transtracheal injections of dexmedetomidine [ 12 ]. They found that dexmedetomidine delivered using a combination of nebulized and transtracheal routes had better patient satisfaction than the intravenous route.…”
Section: Discussionmentioning
confidence: 99%
“…This modality is increasingly being used in anaesthesiology, critical care and pain practice to deliver drugs like antibiotics, dexmedetomidine, lidocaine, morphine and fentanyl. [ 1 2 3 4 5 6 7 8 9 10 11 12 ] This journal has published many manuscripts about using these drugs in the perioperative period for quoted beneficial effects. [ 2 3 4 5 6 7 8 9 10 11 ]…”
mentioning
confidence: 99%